Paracomplex Paracontact Pseudo-Riemannian Submersions. (7th May 2014) - Shukla, S. S.; Verma, Uma Shankar
Abstract : We introduce the notion of paracomplex paracontact pseudo-Riemannian submersions from almost para-Hermitian manifolds onto almost paracontact metric manifolds. We discuss the transference of structures on total manifolds and base manifolds and provide some examples. We also obtain the integrability condition of horizontal distribution and investigate curvature properties under such submersions.